Development of composite material from Recycled Polyethylene Terephthalate and fly ash: Four decades progress review - Mohd Nasir N.H.; Usman F.; Saggaf A.; Saloma (Elsevier B.V., 2023)
Since 1980, numerous studies have been conducted to recycle plastic waste and fly ash into a new material called composite material. This paper aims to evaluate the development of this composite material within four decades of progress review. The evaluation is based on their accomplishments or findings regarding the method used to recycle the Polyethylene Terephthalate PET (RPET) waste to produce the composite materials, mechanical properties, fly ash modification, and previous researcher limitations. In the early 1980s, the researchers investigated the composite potential of the material by polymerizing PET and mixing it with fly ash before the mechanical recycling method discovered in the late 1990s that combined PET flakes with fly ash in an extrusion process to create a composite material. To improve polymer and fly ash compatibility, researchers added a silane coupling agent, used different fly ash particle sizes, and modified the surface with sulfuric acid solutions (5, 10, and 15%) before mixing with RPET. 2022 The Authors